William Tyndale pada Penerjemahan Alkitab dan Implikasinya bagi Teologi Reformed Injili - Andreas Setiawan; Agus Santoso; Bobby Kurnia Putrawan (Sekolah Tinggi Teologi Jaffray Jakarta, 2022)
William Tyndale's efforts to translate the Bible into English had an impact on the spread of the Bible in society and the development of evangelical reformed theology. This article aims to find and provide an introduction to William Tyndale's theology on Bible translation efforts and its implications for evangelical reformed theology. The writing method used is a systematic theological study with descriptive analysis. The results found are that the church is never separated from the people, thus advancing the ministry of the people and having the belief that every devotee has the right to read, understand the Scriptures, and warn teachers and pastors when they deviate. All work is a holy calling and doing it for Christ.